2015
DOI: 10.1111/head.12612
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Headache in Patients With Moderate‐to‐Severe Headache Due to Aneurysmal Subarachnoid Hemorrhage: A Retrospective Cross‐Sectional Study

Abstract: The course of headache in patients with aSAH continuously improved during the 12 months of follow-up. Headache improvement might be expected in patients who were treated with EVT and in those who did not have previous stroke or headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…To determine the prevalence of chronic pain following SAH, a retrospective cross‐sectional study of patients recovering from SAH sampled pain scores from admission, hospital discharge, and at 1, 3, 6, and 12 months thereafter. The authors identified only a mild degree of pain following hospital discharge that subsided over time . Despite differences in demographics and medical management, these studies in concert with the current one collectively indicate that SAH pain can be severe during the days following SAH, but eventually subsides in the weeks to months following the initial onset of headache.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…To determine the prevalence of chronic pain following SAH, a retrospective cross‐sectional study of patients recovering from SAH sampled pain scores from admission, hospital discharge, and at 1, 3, 6, and 12 months thereafter. The authors identified only a mild degree of pain following hospital discharge that subsided over time . Despite differences in demographics and medical management, these studies in concert with the current one collectively indicate that SAH pain can be severe during the days following SAH, but eventually subsides in the weeks to months following the initial onset of headache.…”
Section: Discussionmentioning
confidence: 64%
“…The authors identified only a mild degree of pain following hospital discharge that subsided over time. 20 Despite differences in demographics and medical management, these studies in concert with the current one collectively indicate that SAH pain can be severe during the days following SAH, but eventually subsides in the weeks to months following the initial onset of headache.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The quantitative scale ranges from 0 to 10, with 0 meaning “no headache at all” and 10 meaning “the worst possible headache.” This 11-point scale has been previously applied to headache assessment [79]. We defined NRS scores of 1 to 3, 4 to 6, and 7 to 10 as mild, moderate, and severe headache, respectively.…”
Section: Methodsmentioning
confidence: 99%